Food security in the Sahel: Variable import levy, grain reserves, and foreign exchange assistance - McIntire, John (International Food Policy Research Institute, 1981)
The confluence of droughts and high world grain prices in the late 1960s and early 1970s in the Sahel produced widespread famine, resulting in extensive and displacement of people. The region is extremely poor in normal times and the drought was simply a crisis superimposed on chronic misery. The area has recovered somewhat since 1974 but has made little real progress. There has been, in particular, little growth of real income among agricultural populations, a steep increase of food imports, a high rate of permanent rural emigration (due partly to poor economic opportunities in agriculture), and chronic inflation.